Hubungan Antara Kepribadian Ekstraversi dengan Fear of Missing Out (FOMO) pada Mahasiswa - Alifia Anggeraini; Anggita Krisna Ari Nugraha; Lia Yohana Santoso; Rini Sugiarti; Fendy Suhariadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The study aimed to determine the effect of extraversion personality on the fear of missing out (fomo) in college students. the hypothesis proposed in this study was personality extraversion and fear of missing out (fomo) has an influenced on college students. Research method used in this study is a quantitative method with the proposed variables were fear of missing out (fomo) students as the dependent variable and personality extraversion as the independent variable. subject of this research were college student in Bandar Lampung City. totalling 285 respondents and the method of sampling is using accidental sampling technique. the data of the study were taken Using the fear of missing out (fomo) scale and the extraversion personalities scale, the data collected was analyzed using a simple regression technique the result of the analysis showed that the extraverted personality with fear of missing out (fomo) obtained a correlation coeficient value of 0.782 with the significance value of 0,000 p <0,05 and fear of missing out (Fomo) has an effect of 6 1,2% on extraversion personality p<0,05